Wakaf Esensi Solutif Perbaikan Pendidikan: Jawabah Dilema Lulusan Pendidikan Islam Antara Output, Outcome dan Produk - Hasan H A Buro (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
Failure and deterioration of Islamic education can be seen from the reflection of infrastructure, funds, quality educators who are far from expectations should, resulting in to create output. wakaf has a positive outlook, if it is well managed to improve the quality and progress of Islamic education in the future. This study aims to describe: how wakaf as the essence of solutive improvement of education which is an answer to the dilemma of education graduates between output, outcome and product. This study uses "Library Research". The research data used is secondary data. Data collection techniques used are documentation. Data processing is done by conducting the activity of review, verification and reduction, grouping and systematization, and interpretation or interpretation so that a phenomenon has social, academic, and scientific value. Data analysis in this research is done during and after data collection by using descriptive-critical-comparative method, and content analysis method. From the results of the discussion can be summarized as follows: 1) The future success of each learner should be viewed as a product success (education), not just the success of output or outcome. When the learner is graduated, it is the output of the educational institution in which he or she is studying, but the outcome can immediately overcome his or her life to work (not just get a job). And working, developing a career in the field of work that ditekuninya, in relatively quickly he will appear successful as an educational product. 2) To realize this need to change the public perception of the importance of wakaf as a supporter of Islamic education, as in Egypt with its A-Azhar University, and within its own country, Wakaf Pondok Modern Darussalam Gontor Ponorogo, Wakaf Pesantren Tebuireng in Jombang and Waqf Islamic University Indonesia in Yogyakarta.